Cerebral vasomotor reactivity during hypo- and hypercapnia across the adult lifespan. Issue 3 (March 2020) - Tomoto, Tsubasa; Riley, Jonathan; Turner, Marcel; Zhang, Rong; Tarumi, Takashi
Age is the strongest risk factor for cerebrovascular disease; however, age-related changes in cerebrovascular function are still not well understood. The objective of this study was to measure cerebral vasomotor reactivity (CVMR) during hypo- and hypercapnia across the adult lifespan. One hundred fifty-three healthy participants (21–80 years) underwent measurements of cerebral blood flow velocity (CBFV) via transcranial Doppler, mean arterial pressure (MAP) via plethysmograph, and end-tidal CO2 (EtCO2 ) via capnography during hyperventilation (hypocapnia) and a modified rebreathing protocol (hypercapnia). Cerebrovascular conductance (CVCi) and resistance (CVRi) indices were calculated from the ratios of CBFV and MAP. CVMRs were assessed by the slopes of CBFV and CVCi in response to changes in EtCO2 . The baseline CBFV and CVCi decreased and CVRi increased with age. Advanced age was associated with progressive declines in CVMR during hypocapnia indicating reduced cerebral vasoconstriction, but increases in CVMR during hypercapnia indicating increased vasodilation. A negative correlation between hypo- and hypercapnic CVMRs was observed across all subjects (CBFV%/ EtCO2 : r = −0.419, CVCi%/ EtCO2 : r = −0.442, P < 0.0001). Collectively, these findings suggest that aging is associated with decreases in CBFV, increases in cerebrovascular resistance, reduced vasoconstriction during hypocapnia, but increased vasodilatory responsiveness during hypercapnia.